"Live high, train low" does not change the total "Live high, train low" does not change the total haemoglobin mass of male endurance athletes sleeping at a simulated altitude of 3000 m for 23 nights - Ashenden , M. J.; Gore, C. J.; Dobson, G. P.; Hahn, A. G. (European Journal of Applied Physiology, 1999)
The purpose of this study was to document the effect of 23 days of ``live high, train low'' on the haemoglobin mass of endurance athletes. Thirteen male subjects from either cycling, triathlon or cross-country skiing backgrounds participated in the study. Six subjects (HIGH) spent 8)10 h per night in a ``nitrogen house'' at a simulated altitude of 3000 m in normobaric hypoxia, whilst control subjects slept at near sea level (CONTROL, n = 7). Athletes logged their daily training sessions, which were conducted at 600 m. Total haemoglobin mass (as measured using the CO-rebreathing technique) did not change when measured before (D1 or D2) and after (D28) 23 nights of hypoxic exposure [HIGH 990 (127) vs 972 (97) g and CONTROL 1042 (133) vs 1033 (138) g, before and after simulated altitude exposure, respectively]. Nor was there any difference in the substantial array of reticulocyte parameters measured using automated flow cytometry prior to commencing the study (D1), after 6 (D10) and 15 (D19) nights of simulated altitude, or 1 day after leaving the nitrogen house (D28) when HIGH and CONTROL groups were compared. We conclude that red blood cell production is not stimulated in male endurance athletes who spend 23 nights at a simulated altitude of 3000 m.